Is Hepatitis Delta infections important in Brazil?. Issue 1 (December 2016) - Cicero, Maira; Pena, Nathalia; Santana, Luiz; Arnold, Rafael; Azevedo, Rafael; Leal, Élcio; Diaz, Ricardo; Komninakis, Shirley
Abstract Background The Hepatitis Delta Virus (HDV) can increase the incidence of fulminant hepatitis. For this infection occurs, the host must also be infected with Hepatitis B Virus. Previous studies demonstrated the endemicity and near exclusivity of this infection in the Amazon region, and as a consequence of the difficulty in accessing this area we used dried blood spots (DBS) in sample collection. The aims of this study were to investigate the presence of recombination, to analyze the epidemiology, ancestry and evolutionary pressures on HDV in Brazil. Methods Blood samples from 50 individuals were collected using dried-blood spots (DBS 903, Whatman), and sent via regular mail to Retrovirology Laboratory from Federal University of São Paulo, where the samples were processed. In the analysis the following software were used: PhyML, RDP, BEAST, jModelTest and CODEML. Results Our results confirm the prevalence of HDV-3 in the Amazon region of Brazil, with the absence of inter-genotypic recombination. It was identified a positive selection in probable epitopes of HDV on B lymphocytes that might indicate that the virus is changing to escape the humoral response of the host. The analysis of the time of the most common ancestor demonstrated the exponential growth of this virus in late 1970s that lasted until 1995, after which it remained constant. It was also observed a probable founder effect in two cities, which demonstrate the need to focus on prevention methods against HBV/HDV infection. Conclusion We confirmed the prevalence of HDV-3 in the Amazon region of Brazil, without inter-genotypic recombination. The analysis of the time of the most common ancestor showed that this infection remain constant in the studied area. Taking into account the probable founder effect established in the cities of Rio Branco and Porto Velho, a focus on preventive methods is recommended against these infections.